Rural-Urban disparities in self-reported physical/mental multimorbidity: A cross-sectional study of self-reported mental health and physical health among working age adults in the U.S. - Danielle Rhubart; Jennifer Kowalkowski; Jordan Yerger (Journal of Multimorbidity and Comorbidity)
Purpose Self-rated physical health (SRPH) and self-rated mental health (SRMH) are both linked to excess morbidity and premature mortality and can vary across rural and urban contexts. This can be particularly problematic for rural residents who have less access to important health care infrastructure. In this paper, we assess the prevalence of and rural-urban disparities at the intersection of SRPH and SRMH, specifically self-rated physical/mental multimorbidity (SRPMM) overall and across rural-urban contexts. Methods Using a cross-sectional demographically representative national dataset of over 4000 working age adults in the U.S., we expose rural-urban differences in the prevalence of SRPMM and explore individual-level factors that may explain this disparity. Results Approximately 15 percent of working age adults reported SRPMM, but rural adults were at higher risk than their urban counterparts. However, this disadvantage disappeared for remote rural working-age adults and was attenuated for metro-adjacent rural working-age adults when we controlled for the fact that rural adults had lower household incomes. Conclusion Findings reveal a higher risk of SRPMM among rural adults, in part because of lower incomes among this group. This work acts as the foundation for facilitating research on and addressing rural-urban disparities in SRPMM.